A two year retrospective review of Laparoscopic versus open Appendicectomy in perforated appendix in Hospital Ipoh (June 2006-May 2008) - Krishnan, Nyanamalar (2010)
Appendicectomy is one of the most common general surgical procedures performed all over the world in the surgical department. Since its description by McBurney in 1894 the open approach has become the standard surgical intervention for appendicitis, remaining virtually unchanged for 100 years owing to its proven efficacy and safety. Laparoscopic appendicectomy on the other hand was first performed by Semm in 1983 (Litynski, G.S. 1999).But its popularity increased steadily throughout the 1990s. However, unlike cholecystectomy, the benefits of the laparoscopic approach have not been as apparent for appendicectomy, even more so in perforated appendicitis. Many early randomized trials failed to show any overall benefit for laparoscopy and others at best parity between the 2 procedures. Current studies however indicate a shift in favour of laparoscopy, probably due to the increase in laparoscopic exposure at all levels of surgical training. The aim of this study is to compare certain parameters between Laparoscopic appendicectomy with open appendicectomy. xii RESULTS: Two hundred and five patients with perforated appendicitis were reviewed. Fifty-six patients had laparoscopic appendicectomy and one hundred and forty nine patients had open appendicectomy. The median age in the laparoscopic group was 28 and the open group was 30. The difference in the median age groups was not statistically significant .The p value is 0.310. The mean (s.d) operating time for laparoscopic appendicectomy was 69 minutes (29 minutes).The mean operating time for the open group was 63 minutes (28 minutes). This study showed that there was no significant difference in the mean length of operating time between the two methods. The p value is 0.669. The mean (s.d.) length of hospital stay for the patients in the laparoscopic group was 3.5days (1.6 days). In the open group the mean length of hospital stay was 3.1 days (1.9 days). This was statistically not significant (p=0.382).There was also no statistical significance in the duration the patients took to tolerate orally and for the temperature to settle in both the groups. There were a total of six patients with the surgical site infection and seven who had readmission. Although all 6 patients with surgical site infection were from the open group and none in the laparoscopic group this was not statiscally significant. p = 1.000. Five patients in the laparoscopic group and two in the open group were readmitted within a week of their respective surgeries for ileus. This difference was also not statistically significant with a p value of 1.000.The mean (s.d.) amount of analgesia used in laparoscopic appendicectomy was 387.5mg (259.4mg) . The mean (s.d.) for the use of analgesia in the open group was 274.5mg (204.3mg) for the open group. This was statistically significant where p = 0.006. CONCLUSION: There is no clinically significant difference between laparoscopic appendicectomy and open appendicectomy for perforated appendicitis.